Thymic Stromal Lmphopoietin Pomotes Macrophage-derived Foam Cell Formation - 李大主 王博远 杨保杰 何少林 林静 董江川 吴纯 胡骏 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
The effect of thymic stromal lymphopoietin（TSLP） on macrophage-derived foam cell formation and the underlying mechanism were studied. Macrophages isolated from C57BL/6 mice were co-cultured in vitro with different concentrations of TSLP or TSLPR-antibody in the presence of oxidized low density lipoprotein（ox-LDL）. The effects of TSLP on macrophage-derived foam cell formation were observed by using oil red O staining and intracellular lipid determination. The expression levels of foam cell scavenger receptors（CD36 and SRA） as well as ABCA1 and TSLPR were detected by using RT-PCR and Western blotting. As compared with the control group, TSLP treatment significantly promoted lipid accumulation in macrophages, significantly increased protein expression of CD36 and TSLPR in a dose-dependent manner, and significantly reduced the expression of ABCA1 protein in a dose-dependent manner. No significant differences were noted between the TSLPR-antibody group and the control group. TSLP may down-regulate the expression of cholesterol efflux receptor ABCA1 and up-regulate scavenger receptor expression via the TSLPR signaling pathway, thereby promoting macrophage-derived foam cell formation.